PENGARUH BIAYA KUALITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Kasus pada 16 Perusahaan Manufaktur Sektor Otomotif dan Elektronika di Bursa Efek Indonesia Tahun 2015-2019) - Ela Adiana; Endang Kiswara (Diponegoro Journal of Accounting, 2022)
Quality costs are expenses that arise as a result of the low quality found. Some companies in Indonesia have not been optimal in controlling quality costs, as by indicated the number of complaints from consumers who are not satisfied with the product. This study aims to determine the effect of quality costs on the company’s financial performance. The research sample consisted of 16 automotive and electronics companies listed on the Indonesia Stock Exchange with companies for which all data were available in 2015-2019. This study uses the analysis method PLS with the support of the SmartPLS 3 statistical program. The result showed that the prevention costs had a positive and significant effect on ROI and EPS but an insignificant effect on Tobin’s Q. The appraisal costs had a negative and significant effect on EPS but an insignificant effect on ROI and Tobin’s Q. The internal failure costs had a negative and significant effect on ROI and EPS but an insignificant effect on Tobin’s Q. The external failure costs had a negative and significant effect on EPS but an insignificant effect on ROI and Tobin’s Q. The result of this study provide saveral recommendations for companies to pay attention to the allocation of costs for prevention and appraisal activities, because they can reduce internal failure costs and external failure costs arising from not meeting quality specifications.